Fulfillment of nutrition in adolescent pregnancy - Pertiwi, Nur Fitri Ayu; Laela Abida, Liza; Nurlaili, Helmi (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Pregnancy in adolescence has a high risk for the health of the mother and fetus, one of which is caused by an imbalance in nutritional intake. Pregnant adolescents often do not understand the increased nutritional needs during pregnancy, and are still influenced by physical complaints such as nausea and cultural beliefs related to food taboos. Explaining the fulfillment of balanced nutrition in adolescent pregnancy in the Kalibaru Village Health Center area, North Jakarta. This study used a qualitative approach with a phenomenological design. The main informants were five pregnant adolescents aged 17–19 years, and supporting informants consisted of families, cadres, and midwives. Data were collected through in-depth interviews and analyzed using the Miles and Huberman method. Pregnant adolescents generally eat three meals a day with snacks, with a variety of foods such as vegetables, fruits, fish, and milk. However, nausea in the first trimester is a major obstacle in fulfilling nutrition. In addition, some informants continue to consume foods that are considered taboo due to a lack of understanding of the risks or benefits of these foods. Fulfilling the nutrition of pregnant adolescents still faces challenges from both physical factors (nausea) and socio-cultural factors. Evidence-based nutrition education and assistance involving families and health workers are needed.